Biro Konsultan PR dan Kompetensi Praktisi PR di Era Industrialisasi Komunikasi dan Pencitraan - Dina Sekar Vusparatih (Humaniora, 2013)
The world of communication starts to experience rapid development in various aspects of life, almost all over the world. In Indonesia, it is marked by the emergence of a lot of tv and radio stations, and started the trend of imaging strategy efforts that is used to win the regional election, nasional election, and even to win marketing competition through company’s products or services image branding. This phenomenon is the opportunity for PR consultants to be successful team in designing appropriate communication strategies and appropriate steps to build the image. This opportunity is used by many people which is characterized by the proliferation of consultancies. Competition between consultants becomes so tight considering the companies or organizations that intend to hire consultants also want the best. Competitive bidding process was conducted, to win this, it needs solid team of consultants required in skills and morally. PR competencies of each member are needed to grow into a successful PR consultant.